Alterations of Gastric Microbiota in Gastric Cancer and Precancerous Stages - Zhang, Xinmei; Li, Chao; Cao, Weijun; Zhang, Zhenyu (Frontiers in Cellular and Infection Microbiology, 2021)
Objective Microbial infections have been shown to contribute to gastric carcinogenesis, the knowledge of gastric microbiota alteration in this process may provide help in early diagnosis of gastric cancer. The aim of this study was to characterize the microbial changes and identify taxonomic biomarkers across stages of gastric carcinogenesis. Methods The gastric microbiota was investigated by 16S rRNA gene analysis in gastric mucosal specimens from 47 patients including superficial gastritis (SG), atrophic gastritis (AG), gastric intraepithelial neoplasia (GIN), and gastric cancer (GC). Differences in microbial composition across the disease stages, especially in GIN and GC were assessed using linear discriminant analysis effect size. Results There was no gradual changing trend in the richness or diversity of the gastric microbiota across stages of gastric carcinogenesis. The relative abundance of dominant taxa at phylum and genus levels didn’t show a gradual shift pattern, and the only four taxa that continuously enriched from SG to GC were Slackia, Selenomonas, Bergeyella, and Capnocytophaga, all of which were oral bacteria. The most representative taxa which were enriched in GC patients were oral bacteria including Parvimonas, Eikenella and Prevotella-2, and environmental bacteria including Kroppenstedtia, Lentibacillus, and Oceanobacillus. The gastric microbiota in GIN patients were characterized by enrichment of intestinal commensals including Romboutsia, Fusicatenibacter, Prevotellaceae-Ga6A1-group, and Intestinimonas. Gastric cardia cancer and non-cardia cancer patients had significantly different microbiota profiles characterized by a higher abundance of Helicobacter in the cardia cancer patients. Conclusions Our results provide insights on potential taxonomic biomarkers for gastric cancer and precancerous stages, and suggest that gastric microbiota might play different roles in the carcinogenesis of cardia cancer and non-cardia cancer.